From Heritage to High-Tech : Bridging Culture and Innovation in Learning - Dilah, Tuah (2025)
This paper, From Heritage to High-Tech: Bridging Culture and Innovation in Learning, shows how education can be more engaging and meaningful by combining culture with innovation. Many systems are still rigid, focusing on fixed curricula that limit creativity and make learning less exciting. At the same time, culture risks being left behind if it is not part of the classroom. The paper shares experiences from Universiti Malaysia Sarawak (UNIMAS), including community-based projects, the use of AI and VR for cultural storytelling, the inclusion of Sarawak folk tales in lessons, collaboration across arts and sciences, and alternative assessments such as portfolios and exhibitions. Examples include documenting the Bisaya language and traditional knowledge, as well as creative writing with local writers and poets. These efforts protect cultural heritage while encouraging imagination. The paper concludes that innovation and creativity are not extras, but essential. When culture and learning work together, education becomes a living classroom that can inspire real change.